Biologics in dermatology: Off-label indications - Debdeep Mitra; Ajay Chopra; Neerja Saraswat; Barnali Mitra; Krishna Talukdar; Reetu Agarwal (Wolters Kluwer Medknow Publications, 2020)
Skin and subcutaneous diseases affect millions of people worldwide, causing significant morbidity. Biologics are becoming increasingly useful for the treatment of many skin diseases, particularly as alternatives for patients who have failed to tolerate or respond to conventional systemic therapies. Biological therapies provide a targeted approach to treatment through interaction with specific components of the underlying immune and inflammatory disease processes. Advances in the understanding of disease pathophysiology for inflammatory skin diseases and in drug development have ushered in biologic therapies in dermatology. Biologic therapies are molecules that target specific proteins implicated in immune-mediated disease. This review article highlights the increasing evidence base for biologics in dermatology for off-label use.